Extracellular and subcellular regulation of the PI3K/Akt cassette: new mechanisms for controlling insulin and growth factor signalling. (20th March 2007) - Wilson, C.; Vereshchagina, N.; Reynolds, B.; Meredith, D.; Boyd, C.A.R.; Goberdhan, D.C.I.
Abstract : The PI3K (phosphoinositide 3-kinase)/Akt (also called protein kinase B) signalling cassette plays a central role in the response to growth factors, particularly insulin-like molecules, and its misregulation is a characteristic feature of diabetes and many forms of human cancer. Recent molecular genetic studies initiated in the fruitfly, Drosophila melanogaster, have highlighted two new cell-type-specific mechanisms regulating PI3K/Akt signalling and its downstream effects. First, the cellular response to this cassette is modulated by several classes of cell-surface transporters and sensors, suggesting an important role for extracellular nutrients in insulin-sensitivity. Secondly, various cell types show a markedly different subcellular distribution of the activated kinase Akt, influencing the cellular functions of this molecule. These findings reveal new mechanisms by which processes such as growth, lipogenesis and insulin resistance can be differentially regulated and may suggest novel strategies for treating insulin-linked diseases.